2022
DOI: 10.3390/buildings12091322
|View full text |Cite
|
Sign up to set email alerts
|

Resilient Capabilities to Tackle Supply Chain Risks: Managing Integration Complexities in Construction Projects

Abstract: Due to the increased globalization and the disruptions caused by pandemics, supply chains (SCs) are becoming more complex in all industries. Such increased complexities of the SCs bring in more risks. The construction industry is no exception; its SC has been disrupted in line with its industrial counterparts. Therefore, it is important to manage the complexities in integrating SC risks and resilient capabilities (RCs) to enable a resilient SC in construction. This study investigated the complexity involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…However, it is evident that developing countries are leading in CSCR research. This confirms the observation by Malik et al. (2022) that although SC disruptions have severely affected different countries in the world, the effects are more pronounced in developing countries.…”
Section: Review Findings and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, it is evident that developing countries are leading in CSCR research. This confirms the observation by Malik et al. (2022) that although SC disruptions have severely affected different countries in the world, the effects are more pronounced in developing countries.…”
Section: Review Findings and Discussionsupporting
confidence: 90%
“…Identifying the most prevalent risk factors is crucial for implementing appropriate mitigation measures, as all construction projects share some common risk factors along their supply chains (Wuni et al, 2019). Previous studies (see Malik et al, 2022;Rudolf and Spinler, 2018) have demonstrated a necessity to identify those supply chain risks that are most likely to occur on construction projects. Contextually, the DRFs in this study refer to the construction project supply chain risks that have been mostly reported in research over the past 20 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paper [46] also reviews that based on the supply chain field, SD has been applied in Agri/aquaculture, daily tools, automotive, biofuels, electronic products, food and beverages, woodworking, mining, transportation, and utility. This method is not new in the construction sector's supply chain modeling approach; it is used to build a green strategy evaluation model [47][48][49], construction supply chain risk [50], circular issue [51,52], and prefabricated construction supply chain product [53,54]. As primary construction materials, Previous studies of the supply chain of aggregate andesite stone products and their derivatives are limited on analyzed the network design and production planning with linear mix integer programming.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It allows stakeholders to make informed choices, allocate resources wisely, and maintain a structured approach throughout the project's lifecycle (Bhyan et al, 2023). In summary, project risks are integral to understanding and managing the uncertainties associated with a housing project's success, and proactive risk management is essential for its smooth execution (Malik et al, 2022).…”
Section: Project Risksmentioning
confidence: 99%